Kelayakan kualitas air untuk budidaya ikan Kuwe (Caranx sp.) pada kurungan jaring apung di Perairan Kelurahan Makawidey - Mamesah, Yulia; Undap, Suzanne L.; Tumembouw, Sipriana S.; Kusen, Diane J.; Pangemanan, Novie PL.; Monijung, Revol D. (Universitas Sam Ratulangi, 2023)
Abstract The aim of study was to determine the feasibility of the quality of Kuwe fish (Caranx sp.) aquaculture waters in floating net cages (KJA) in Makawidey Village, Bitung City. The research method used was purposive with primary data (water quality data: brightness, temperature, depth, salinity, pH, DO) and secondary data (various existing documents and literature that can support research). Prior to data collection, a preliminary study was carried out to determine the research point. The data obtained during the research were analyzed and displayed in the form of tables and graphs and presented descriptively. The results of measuring water quality parameters are; Brightness (Point 1: 2,5 m ; Point 2: 3,1 m ; Point 3: 3,3 m), Depth ( Point 1 : 2.7 m ; Point 2: 9 m ; Point 3: 26,80 m); Temperature (Point 1: 28.40 ± 1.35; Point 2: 27.48 ± 0.90C; Point 3: 27.31 ± 1.36) ; Salinity (Point 1: 31.59±14.5 ; Point 2: 31.57±14.6; Point 3: 31.55±14.6 ppt); pH (Point 1: 8.90±4.9; Point 2: 7.43±3.44; Point 3: 7.20±3.29) and Dissolved Oxygen (Point 1: 9.60±4.39; Point 2: 9.13 ± 4.25; Point 3: 9.13 ± 4.20 mg/l), has a value that is in accordance with seawater quality standards stipulated in Government Regulation Number 22 of 2021 concerning Implementation of Protection and Management Environment. Makawidei waters meet the requirements to be used as a location for aquaculture in terms of water quality parameters and produce a suitable category for aquaculture biota. Keywords: waters environment, psycho-chemical parameters, site selection, sea farmingAbstractThe aim of study was to determine the feasibility of the quality of Kuwe fish (Caranx sp.) aquaculture waters in floating net cages (KJA) in Makawidey Village, Bitung City. The research method used was purposive with primary data (water quality data: brightness, temperature, depth, salinity, pH, DO) and secondary data (various existing documents and literature that can support research). Prior to data collection, a preliminary study was carried out to determine the research point. The data obtained during the research were analyzed and displayed in the form of tables and graphs and presented descriptively. The results of measuring water quality parameters are; Brightness (Point 1: 2,5 m ; Point 2: 3,1 m ; Point 3: 3,3 m), Depth ( Point 1 : 2.7 m ; Point 2: 9 m ; Point 3: 26,80 m); Temperature (Point 1: 28.40 ± 1.35; Point 2: 27.48 ± 0.90C; Point 3: 27.31 ± 1.36) ; Salinity (Point 1: 31.59±14.5 ; Point 2: 31.57±14.6; Point 3: 31.55±14.6 ppt); pH (Point 1: 8.90±4.9; Point 2: 7.43±3.44; Point 3: 7.20±3.29) and Dissolved Oxygen (Point 1: 9.60±4.39; Point 2: 9.13 ± 4.25; Point 3: 9.13 ± 4.20 mg/l), has a value that is in accordance with seawater quality standards stipulated in Government Regulation Number 22 of 2021 concerning Implementation of Protection and Management Environment. Makawidei waters meet the requirements to be used as a location for aquaculture in terms of water quality parameters and produce a suitable category for aquaculture biota.Keywords: waters environment, psycho-chemical parameters, site selection, sea farming